TIME MANAGEMENT AND ORGANIZATIONAL PRODUCTIVITY IN INNOSON NIGERIA LIMITED - Achilike, Nicholas I. (African Journal of Social and Behavioural Sciences, 2025)
The study investigated Time management and organisational productivity in Innoson Nigeria Limited. The specific objectives of the study were to: examine the relationship between scheduling and operational efficiency; ascertain the extent of the relationship between delegation and output; and investigate the relationship between timely budgetary allocation and the designated timeframe in Innoson Nigerian Limited. The study used a descriptive survey design. The population of the study was two hundred (200) staff of Innoson Nigerian Limited. The entire population was studied due to its small size. The Z-test statistical tool was used to test the hypotheses. The findings indicated that Scheduling had a significant positive relationship with operational efficiency (Z = 8.005, P = .001). Delegation had a significant positive relationship with output, as indicated by a Z-test (Z = 9.082, P = .001). Timely budgetary allocation has a significant positive relationship with the designated timeframe of Innoson Nigeria Limited, as indicated by a Z-test (Z = 9.010, P = .001). The study’s findings indicate that Scheduling, delegation, Timely budgetary allocation, and Deadline setting had a significant positive relationship with operational efficiency, output, adherence to the designated timeframe, and meeting targets at Innocent Nigeria Limited. The study therefore concludes that effective time management enhances employee performance, minimizes delays, reduces waste, and enables the company to meet targets consistently, especially in areas such as supply chain coordination, vehicle assembly, and client delivery timelines. To maintain high productivity, Innoson should apply principles such as goal-setting, prioritization (Pareto Principle), and task delegation, ensuring that workers focus on high impact tasks.